Between the Falchion and the Sword: a Side Arms Specimen from the Naval Museum in Gdynia - Piotr Strzyż (Fasciculi Archaeologiae Historicae)
This paper discusses a falchion of unknown provenance kept in the Naval Museum in Gdynia. It is an example of a side arms characterised by both its hilt, specific to so-called ‘Moravian’ falchions and, most importantly, its double-edged sword blade bearing a mark in the form of a circle with an inscribed cross and the letter ‘S’. Based on typological and chronological analysis, the artefact can be dated to the second half of the 15th century.